Identification and Validation of an Immune-Related eRNA Prognostic Signature for Hepatocellular Carcinoma - Cai, Shenglan; Hu, Xingwang; Chen, Ruochan; Zhang, Yiya (Frontiers in Genetics, 2021)
Background: Enhancer RNAs (eRNAs) are intergenic long noncoding RNAs(lncRNAs) that participate in the progression of malignancies by targeting tumor-related genes and immune checkpoints. However, the potential role of eRNAs in hepatocellular carcinoma(HCC) is unclear. In this study, we aimed to construct an immune-related eRNA prognostic model that could be used to prospectively assess the prognosis of patients with HCC. Methods: Gene expression proﬁles of patients with HCC were downloaded from The Cancer Genome Atlas(TCGA).The eRNAs co-expressed from immune genes were identified as immune-related eRNAs. Cox regression analyses were applied in a training cohort to construct an immune-related eRNA signature (IReRS), that was subsequently used to analyze a testing cohort and combination of the two cohorts. Kaplan-Meier and receiver operaring characteristic(ROC) curves were used to validate the predictive effect in the three cohorts. Gene Set Enrishment Analysis(GSEA) computation was used to identify an IReRS-related signaling pathway. A web-based cell type identification by estimating relative subsets of RNA transcripts (CIBERSORT) computation was used to evaluate the relationship between the IReRS and infiltrating immune cells. Results: A total of 64 immune-related eRNAs (IReRNAs) were identified in HCC, and 14 IReRNAs were associated with overall survival (OS). Next, five IReRNAs were used to construct the IReRS, which was correlated with poor survival and was an independent prognostic biomarker of HCC. The GSEA results showed that the IReRS was correlated to cancer-related and immune-related pathways. Moreover, we found that IReRS was correlated to infiltrating cells, including CD8+ T cells and M0 macrophages. Finally, the expression and prognosis of the five risk eRNAs in tumor tissues and adjacent normal tissues was verified, and AL445524.1 may function as oncogene and affect prognosis partly by regulating CD4-CLTA4 related genes. Conclusion: Our results suggest that the IReRS could serve as a biomarker for predicting prognosis in patients with HCC. Additionally, it may be correlated to the tumor immune microenvironment and could be used as the biomarkers in immunotherapy for HCC.